Implications of Victim Protection in Handling Crimes of Sexual and Monothesis Against Minors - M. Candra Gunawan Sitorus; Parameshwara Parameshwara; Bachtiar Simatupang; Erniyanti Erniyanti; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The handling of the crime of sexual intercourse and molestation of minors is a crucial issue that requires serious attention from various parties. The background of this study is the high rate of sexual violence against minors in the Barelang Police area and the need to evaluate the implementation of victim protection in this context. The purpose of this study is to analyze the implications of victim protection in handling the crime of sexual intercourse and molestation of minors in the Barelang Police, as well as to identify obstacles and efforts made to improve this protection. The research method used is normative juridical through library research using secondary data, and also uses an empirical juridical approach through field research using primary data collected through interviews with law enforcement officials, psychologists, victims, and victims' families. Secondary data was obtained from official documents of the Barelang Police, case reports, and related literature. Data analysis was carried out using qualitative descriptive methods to provide a comprehensive picture of the condition of victim protection and its implications. The results of the study show that although there are serious efforts by the Barelang Police in providing protection to victims, there are several significant obstacles that reduce the effectiveness of these protections. The main obstacles include a lack of adequate psychological assistance, lengthy and convoluted legal processes, a lack of public awareness, and ineffective coordination between related institutions. The implications of these barriers include prolonged psychological suffering for victims, a decline in public trust in the justice system, and a lack of justice for victims. Suggestions given to overcome these obstacles include: capacity building and training of law enforcement officials, education and awareness campaigns in the community, and strengthening victim protection systems and facilities by the government. It is hoped that with the implementation of these suggestions, victim protection can be improved, so that justice and welfare for children victims of sexual violence can be realized more optimally.